Wave energy at coastal area off Lahad Datu Town, Sabah - Ahmad Saifullah Mazlan (2008)
Wave energy is natural phenomenon that shaping the structure of the coastal area. The modelling of the wave energy at the coastal area off Lahad Datu town was carried based on data from April 2000 until March 2005. The study towards the wave energy distribution within the area was taken into account the bathymetry structure of the particular area Objectives of the study are to model the wave energy at the coastal area off Lahad Datu town, to generate the bathymetry maps of the coastal area, and to determine the geomorphology features that affected by the wave energy. This study was done by collecting the secondary data from the government agencies such as Meteorological Department and private agencies. Data then were analysed by applying the Longinov (1966) wave energy equation. The obtained data also were analyse by using the Surfer 7 software to obtain the bathymetry and the wave energy distribution data. The results from the analysis showed that the wave energy within the area mere affected by the features of the seafloor bathymetry. The wave energy that refracted towards the coastline dissipates as it near the coastal area Beside that the existence of the coastal geomorphology such as mangroves, group of islands at the eastern part of the studied area support that the wave energy was relatively low within the area The low wave energy is considered safe within the area and this encourages the coastal development. However, any changes increased in the wave energy will give great impact towards the coastal area